IMPLEMENTASI PENDEKATAN METODE DESIGN THINKING SISTEM PERSURATAN ONLINE BERBASIS MOBILE DAN WEB BASE - Mahardika, Fajar; Bambang Sumatri, Raden Bagus; Ratih, Ratih (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
The application of the Design Thinking method in the development of a mobile web-based online mail system aims to increase efficiency and convenience in creating, managing, and sending letters digitally. Design Thinking, as an approach that focuses on solving problems by understanding user needs in depth, is used to design more intuitive and user-centric solutions in online correspondence systems. This approach consists of five main stages: empathy, problem definition, ideation, prototyping, and testing, all of which have an important role to play in creating mobile web applications that are accessible, secure, and meet user needs, both in terms of functionality and user experience. In the ideation stage, various concepts and features that can improve efficiency, such as automated mail delivery, cloud-based mail archive management, and electronic notifications and verification, were developed. In the prototyping stage, the design of the interface and basic functions of the application is created which is then tested by involving users to obtain feedback that can improve the system. Testing is carried out on an iterative basis, with a focus on testing functionality and user experience, to ensure that the application can be used effectively and efficiently. The results of the implementation show that this system can increase the speed and ease of digital mail management and provide a better user experience compared to conventional mail systems